BETON MUTU TINGGI TANPA PROSES PEMADATAN MANUAL - Anni Susilowati; Pratikto _ (Jurnal Poli-Teknologi, 2012)
The need of the advanced infrastructure facilities, such as long-span concrete bridges , high-rise concrete buildings should be considered as the new concrete development. Improving the quality of concrete can be done with a material change or replacement of some materials with steel slag. The recent time many industry take a part in using waste material from Cilegon steel. In Indonesia, high quality concrete compressive strength can be achieved a maximum strength about 60 MPa. Concrete properties will decrease as a result of the added material strength of cement, aggregates, and the presence of pores. Water cement ratio reduction (w/r) and the addition of admixture as silicafume often used to modify the composition of the concrete and reduce pores. W/r reductions result in reduced porosity and the pores of the concrete, but workability concrete also be difficult to do. In order to make concrete workable the used superplastisizer is the best solution to do. Small water cement ratio 0.2 and superplasticizer intramix kind High Range water reduction at a dose of 1.8% can produce high-performance concrete. In the cement composition 1217kg, 243kg of water, sand 446kg, 545kg steel slag, superplasticizer silicafume 24l 85kg and obtained high quality concrete with compressive strength of 588.53 kg/cm2 in slump flow with the weight of 2230kg/m3 64mm. Principles of compaction without using a vibrator to use a substance without reducing the quality of the concrete risers. Small factors of w/r requires careful stirring using a saturated aggregate surface is helpful meaning in manufacture high quality concrete. Keyword : High Strength concrete, superplasticizer, steel slag, water cement ratio, slumpflow.